The psychological impact of diagnosis of sinonasal, nasopharyngeal, and laryngeal cancers: a systematic review - Bonafede, Michela; d'Errico, Angelo; Rugarli, Sabrina; Mensi, Carolina; Miligi, Lucia; Calisti, Roberto; della Gatta, Rosa; Piro, Sara; Melis, Paola; Vasselli, Donatella; Binazzi, Alessandra (Frontiers in Psychology, 2024)
Objective High risk of degraded quality of life and psychological distress is observed in patients diagnosed with sinonasal, nasopharyngeal, and laryngeal cancers, which could be caused by exposure to carcinogens in workplaces. This review aimed to investigate the psychological impact of diagnosis associated with the possible occupational etiology of such neoplasms and to explore the instruments that evaluate the quality of life (QoL), anxiety, and depression in these patients. Methods Studies were considered for the review only if they described aspects of the psychological impact of the diagnosis of sinonasal, nasopharyngeal, and laryngeal cancers and reported results distinguished by the tumor site. The psychological impact was assessed in terms of health-related QoL, anxiety, and depression using reliable psychometric questionnaires administered at the time of diagnosis and 1 year later. Results In more than 5,900 records identified, 442 studies fulfilled the eligibility criteria and 436 were excluded after full-text screening, resulting in six studies to be finally included in the review. The EORTC Core Quality of Life questionnaire (EORTC QLQ-C30), EORTC QLQ-H&N35, and Functional Assessment of Cancer Therapy (FACT) were used to evaluate the QoL, whereas the Hospital Anxiety and Depression Scale (HADS) and Center for Epidemiologic Studies Depression Scale (CES-D) questionnaires were employed to assess anxiety and depression. QoL scores were similar to those of the general population at the time of diagnosis and remained unchanged or slightly improved at 1 year since diagnosis. In contrast, a higher prevalence of anxiety and depression was observed compared with the general population, although the results were inconsistent across the very few studies identified. No study investigating the association between the potential occupational etiology and QoL or distress was found. Conclusion Exploring the existing scientific literature on emotional distress in sinonasal, nasopharyngeal, and laryngeal cancer patients was prompted by concerns over the disfiguring nature of treatment and the additional emotional burden resulting from their occupational etiology. Unfortunately, neither a crucial element nor other risk factors (lifestyle, smoking, drinking, etc.) were examined in any study. Patients' employment history should be considered in order to assess the possible impact of believing they are affected by an occupational exposure disease in the evaluation of their psychological distress. This history would support evidence-based recommendations about dedicated psychological interventions.